Pengembangan Materi dan Metode Pembelajaran Selantang untuk Pemberdayaan Lansia Kelurahan Mojolangu Malang - Sonhaji, Sonhaji; Sa’adah, Lailatus; Andiani, Lidia; Saputra, Achbar Adi; Nissa, Khoirun (Jurnal ABM Mengabdi, 2025)
This activity aims to help empower the Elderly Family Development through Selantang, Mojolangu Village, Lowokwaru District, Malang City. Activities include designing an effective curriculum and learning methods according to the characteristics of the elderly community. Learning materials include the dimensions of resilient elderly, from physical to spiritual dimensions. The methods used are training and implementation assistance for Selantang members. Learning activities use “angklung” as a medium. Members are invited to use it as a means of entertainment and learning as well as reflection and management of emotions connected to spirituality. This activity produces a curriculum and learning method guidebook and learning facilities with the principle of "Learning Happily". The Elderly Family Development administrators and Selantang members not only gain knowledge and learning techniques, they can also practice managing emotions and spirituality in their daily lives and can feel more peace and calm, strengthen gratitude, and get closer to God. They are also enthusiastic about maintaining a balance between physical, emotional, and spiritual health